Tattoos and the vulnerability to STD-Aids in female prisoners - Giordani, Annecy T.; Bueno, Sônia M.V. (Brazilian Journal of Sexually Transmitted Diseases, 2002)
Background: It is observed that many of those people excluded by society are tattooed. Their tattoos arc most often made under poor hygiene conditions and by using inadequate material. The meanings and communication power of such tattoos awaken the interest of those who have been marginalized, including female prisoners. Objectives: To correlate inadequate practices in tattooing to the transmission of HI V and other infectious agents; to orientate subjects to more adequate behaviors in these situations, aiming at self-protection and knowledge multiplication in and out of prisons. Methods: We worked with 17 prisoners in three public women’s prisons in the interior of São Paulo State. Fourteen of such women had tattoos. A humanistic and qualitative action-research was developed according to ethical precepts and scientific rigor. The subjects’ accounts were recorded on cassette tapes and later transcribed. Photographs of the tattoos were taken after written consent was obtained from the subjects. Results: Most of the tattoos were located on the legs, arms and breasts. They had been made at different times and places. Almost all of them had been made at home using improvised equipment and only one had been produced with a sewing needle in the prison. Most of the subjects reported that they had them simply because they liked them. Almost half of the tattoos consisted of the names and the initials of the women’s partners, floral subjects, cupids and hearts. Most of the prisoners reported that their tattoos did not have a special meaning. Two of the subjects were homosexuals and partners in the same cell. Conclusion: The tattoos denoted the association with lovers who. in addition to being partners in the use of injectable, were also their tattoo makers. All of them were vulnerable to infection by HlV-aids and other bloodborne and sexually transmitted infectious agents.